Study on Fiscal Imbalance of Tamil Nadu, India - R. Sivakumaresan*, A. Udhayakumar and (Journal of Experimental Sciences, 2011)
The study focused on Fiscal imbalance and its adverse effects on macroeconomic equilibrium in India have been receiving wide attention; the issue at States’ level has not so far been adequately analyzed. In many respects, fiscal situation in States is more critical than that at the Centre as States have the Constitutional responsibility for providing basic social and economic services, yet, do not have independent power to borrow from the market or the central bank. Given these constraints, the burden has tended to fall on capital and maintenance expenditures with adverse implications emphasizes the differences between fiscal sustainability analysis at the national and sub national levels, attempts to take into account uncertainty, and discusses the key components of the state’s fiscal accounts and how they respond to reforms and shocks. Risks to Tamil Nadu’s fiscal outlook include interest rate shocks, pressures on the primary balance, and contingent liabilities.